Studies of atmospheric aerosols in the Russia Arctic regions - L. P Golobokova; V. V. Polkin; D. M. Kabanov; S. A. Terpugova; D. G. Chernov; E. V. Chipanina; T. V. Khodzher; O. G. Netsvetaeva; M. V. Panchenko; S. M. Sakerin (Лëд и снег, 2015)
Chemical composition of snow and ice in the Arctic depends, to a considerable extent, on chemical composition of aerosol particles. Analysis of atmospheric aerosol characteristics in the boundary layer near Arctic settlements Tiksi (Summer 2010) and Barentsburg (Spring–Summer 2011) have been investigated. The results contain the outcome of number concentration measure (NA), aerosol optical thickness of the atmosphere, and chemical composition of the water soluble aerosol fraction. Level of aerosol concentration in the boundary layer of the tested points is rather low, and characterized by the following number concentration values: in Tiksi –NA = 1,80±4,5 μg∙cm−3, in Barentsburg – spring – 4,95±3,49 μg∙cm−3, summer – 3,66±3,13 cm−3. Aerosol optical thickness of the atmosphere is characterized by rather low values, and low changeability as compared with continental areas of middle latitudes. Seasonal changes in the aerosol optical thickness of the atmosphere near Barentsburg conforms with earlier obtained data in the Arctic regions. Mean value of Ångstrom selectivity indicator amounted to 1.28 in spring, and to 1.42 in summer. Mean total concentration of ions in aerosols near Tiksi (2.4±1.6 μg∙m−3) is quantitatively correlated with ions total in aerosols near Barentsburg for spring season (2.8±1.4 μg∙m−3). In the water soluble fraction of aerosols is dominated the concentration of ions both marine (Na+, Cl−), and continental (NH4+, SO42−, NO3−) origin. Chemical composition of aerosols in Tiksi and Barentsburg is similar to aerosols composition in the Antarctic coast regions.